Development of an in situ polymerized artificial layer for dendrite‐free and stable lithium metal batteries - Rui Tan (Battery Energy, 2024)
Severe lithium dendrite issues bring a significant challenge for the practical application of Li metal anodes. In this study, a scalable spray-coating method is used to in situ construct an organic/inorganic composite interfacial layer including Li-Zn alloy and lithium polyacrylate on the surface of lithium metal. The Li-Zn alloy exhibits favorable lithiophilic and high Li+ diffusion coefficient, whereas highly elastic lithium polyacrylate is a Li+ conductor and provides excellent mechanical properties. Finally, the ZA-Li||ZA-Li cell shows stable cycling for over 1800 h with 1 mA cm−2 at 2 h per cycle, which demonstrates a pronounced inhibition of lithium dendrite growth. Based on the above merits, this work would open a new avenue to develop advanced artificial interfacial layer with multiple capabilities for high-performance lithium metal batteries.